ENHANCING EFL READING COMPREHENSION SKILLS THROUGH PROBLEM-BASED LEARNING: EVIDENCE FROM STUDENT ENGAGEMENT AND STRATEGY USE - Ayiz, Abdul; Yudhi Nugroho, Kurniawan (Acceleration: Multidisciplinary Research Journal, 2025)
Reading comprehension remains one of the most essential yet challenging skills for English as a Foreign Language (EFL) learners. Traditional reading instruction often emphasizes teacher-centered approaches that limit students’ active involvement in meaning-making. This study investigates the impact of Problem-Based Learning (PBL) on enhancing EFL students’ reading comprehension skills, engagement, and strategy use. A quasi-experimental design was employed with two groups of undergraduate EFL learners: an experimental group (n = 35) receiving PBL-based reading instruction and a control group (n = 35) taught through traditional teacher-led methods. Data were collected using a reading comprehension test, an engagement questionnaire, and a reading strategies inventory. Results revealed that the PBL group achieved significantly higher post-test scores than the control group, indicating improved reading comprehension performance. Moreover, PBL fostered greater behavioral, emotional, and cognitive engagement, alongside the increased use of higher-order reading strategies such as inferencing, summarizing, and critical questioning. These findings suggest that PBL provides a more interactive and meaningful framework for teaching reading, enabling learners to become active participants in constructing textual meaning. The study highlights pedagogical implications for EFL educators, recommending the integration of real-world problems into reading instruction to enhance comprehension outcomes.